Comparing the nature of the western and eastern Azores mantle. (1st January 2016) - Genske, Felix S.; Beier, Christoph; Stracke, Andreas; Turner, Simon P.; Pearson, Norman J.; Hauff, Folkmar; Schaefer, Bruce F.; Haase, Karsten M.
Abstract: The Azores islands in the central North-Atlantic originate from a regional melting anomaly, probably created by melting hot, unusually hydrous and geochemically enriched mantle. Here, we present Hf, Pb and Os isotopic data in geochemically well-characterised primitive lavas from the islands Flores and Corvo that are located west of the Mid-Atlantic Ridge (MAR), as well as submarine samples from a subsided island west of Flores and from Deep Sea Drilling Project (DSDP) holes drilled in the western part of the Azores platform and beyond. These are compared to existing data from the Azores islands east of the MAR. The geodynamic origin of the two islands west of the ridge axis and furthest from the inferred plume centre in the central part of the plateau is enigmatic. The new data constrain the source compositions of the Flores and Corvo lavas and show that the western and eastern Azores mantle is isotopically similar, with the exception of an enriched component found exclusively on eastern São Miguel. Trace element ratios involving high field strength elements (HFSE) are distinctly different in the western islands (e.g. twofold higher Nb/Zr) compared to any of the islands east of the MAR. A similar signature is observed in MAR basalts to the south of the Azores platform and inferred to originate from (auto-) metasomatic enrichment of the sub-ridge mantle (Gale et al., 2011, 2013). In a similar fashion, low degree melts from an enriched source component may metasomatise the ambient plume mantle underneath the western Azores islands. Melting such a modified plume mantle can explain the chemical differences between lavas from the western and eastern Azores islands without the need for additional plume components. Recent re-enrichment and intra melting column modification of the upwelling mantle can cause local to regional scale geochemical differences in mantle-derived melts.